Application of Self Control Techniques in Reducing Selfharm Behavior in Adolescents - Juli Arya Mustika; Manah Rasmanah; Bela Janare Putra (Konsultan Jurnal Ilmiah Indonesia, 2024)
This research is in the background of the rampant phenomenon of self-harm, a behavior to calm down by using ways of self-harm or self-harm, this behavior is dangerous and needs to be overcome, the self-harm behavior of client